Fabrication of Attapulgite Coated Membranes for Effective Separation of Oil‐in‐Water Emulsion in Highly Acidic, Alkaline, and Concentrated Salty Environments. Issue 16 (26th May 2017) - Li, Jian; Zhao, Zhihong; Shen, Yongqian; Feng, Hua; Yang, Yaoxia; Zha, Fei
Abstract : Facile and eco‐friendly methods to fabricate novel materials for effective separation of oil‐in‐water emulsion in harsh conditions are urgently desired. Here, attapulgite (APT) coated polyvinylidene fluoride (PVDF) membranes with underwater superoleophobic property are fabricated by simply leaching APT suspension onto a PDVF membrane using a vacuum pump. More importantly, such membrane possesses outstanding separation capability with separation efficiency higher than 99.2% for oil‐in‐water emulsions not only in mild environments but also in highly acidic, alkaline, and concentrated salty environments. The outstanding chemical stability under harsh environments including strong acidic, alkaline, and concentrated salty conditions makes the membrane become a promising candidate for treatments of industrial wastewater containing emulsified oil/water mixtures in the future. Abstract : An underwater superoleophobic APT‐coated membrane is fabricated by leaching APT and sodium alginate suspension onto a PVDF membrane using a vacuum pump. The as‐prepared membrane can effectively separate oil‐in‐water emulsions in highly acidic, alkaline and concentrated salty environments.